Surface initial clitic placements in Slovene (and other South Slavic languages) - Peti-Stantić, Anita (2007)
The authors adopt the standard approach to Slovene pronominal (me, te, se, ga, jo...) and verbal (sem, si, je... ) clitics seen as special clitics in Zwicky's 1977 clitic typology as being prosodically either enclitic, integrating into the prosodic phrase of the pohnological word to their left or proclitic, cliticizing onto the ponological word to their left (Golden 2003). Such an assumtion is based on their ability to occur in the second, as well as in the initial position in the surface structure. We argue that there are syntactic restrictions to the initial clitic placement Slovene and clasify them in four types of syntactic contexts which allow initial placement in the surface structure. 1. Elliptical sentences: 1.1.1. Te lahko pokličem v službo? youCL-acc may call in office 'May I call you to the office?' 1.1.2. (Ali) te lahko pokličem v službo? (If) youCL-acc may call in office 'May I call you to the office?' 1.1.3. Lahko te pokličem v službo. may youCL-acc call in office 'I can/may call you to the office.' 2. Clitic following the direct speech: 2.1.1. « ; Ne moreva ga pustiti tukaj, » ; mu je mirno in podjetno govorila Katarina. '» ; We can't leave him here, « ; Catherine said to him calmly and energetically.' 2.1.2. *» ; Ne moreva ga pustiti tukaj, » ; mirno mu je in podjetno govorila Katarina. '» ; We can't leave him here, « ; Catherine said to him calmly and energetically.' 3. Clitic placement conditioned by an inversion of a subordinate clause: 3.1.1. Če kaj najdeš, mi sporoči! if something find2sg meCL-dat let-know 'If you find something, (please, ) let me know!' 3.1.2. Sporoči mi, če kaj najdeš! let-know meCL-dat if something find2sg '(Please, ) let me know, if you find something, !' 3.1.3. *Mi sporoči, če kaj najdeš. meCL-dat let-know if something find2sg 'Let me know, if you find something, !' 4. Clitic placement after the conjunction in (or other copulative or adversative conjunctions) 4.1.1. Stregel je kavo in me gledal. servePast3sg coffee and meCL-acc watchPast3sg 'He served coffee and watched me.' 4.1.2. *Stregel je kavo in gledal me. servePast3sg coffee and watchPast3sg meCL-acc 'He served coffee and watched me.' We have to mention that all these types illustrated by pronominal clitics also allow the verbal clitics in the same positions. The fourth type, which is, because of examples such as Slekel si je plašč in (si) sezul čevlje ter (si) nataknil copate. ('He took off his coat and (took off) his shoes and put on his slippers.') somewhat different in this respect, will be discussed in depth. By comparing such examples to possible placements in colloquial speech of typollogicaly close Croatian and typollogically distinct Bulgarian there will be shown that in South Slavic languages there is a syntactic pattern of historical changes which allow such surface positions no matter of a prosodic structure of a given language.